Julian of Norwich: a comprehensive bibliography and handbook - Morris, Teresa D.; Holloway, Julia Bolton (Edwin Mellen Press, 2010)
J. Time and SpaceJ. I: Timeline; J. II: Maps; K: Electronic Julian; L: Bibliographies and Surveys; Index.